Stem injection of different nitrogen forms into young Norway spruce - Petersson, Anna (2012)
This master thesis has been a pilot study preceding a forthcoming project of a larger scale with the long term objective to separate the direct effect of added nitrogen on soil processes from indirect effects via trees. The aim of this study has been to investigate the allocation of nitrogen following direct injection of liquid solutions into the xylem of 40 year old Norway spruce. The field site is located at Flakaliden (64°07’N, 19°27’E), approximately 60 km northwest of Umeå, Sweden. A total of 18 trees were selected for treatment, equally divided between three treatments, potassium nitrate, glutamine and water (control). The solutions were labelled with 15N in order to enable assessment of how the injected nitrogen compounds are distributed within the crown, as well as speed of translocation. Allocation was measured over time during three subsequent sampling occasions as well as through spatial distribution in the canopy. Needle samples were taken on two different levels and four different directions within the crown of each tree, at three subsequent sampling occasions after stem injection on August 25, 2009. Needles were analysed through an EA-IRMS (Elemental Analyzer - Isotope Ratio Mass Spectrometer), for atom percent 15N and total nitrogen concentration. No significant differences were found regarding sampling direction or interactions between sampling direction and level, treatment nor sampling occasion. For neither of the treatments was labelled nitrogen detected anywhere in the foliage until the second sampling occasion, 13 days after stem injection. Labelling was consistently significantly higher for the trees treated with nitrate compared to the trees treated with glutamine and more labelled nitrogen was detected in the lower third of the foliage compared to the upper third. For the glutamine treatment only the lower canopy was successfully labelled. No significant increases for either level between the second or the third sampling occasion were detected. Considerable rises in atom percent 15N were detected for both treatments but not in total nitrogen concentrations. A comparison between the theoretical increases in nitrogen concentrations, based on the amount of added nitrogen, and the observed increases showed that the theoretical increase for both crown levels were considerably higher than the achieved rise in nitrogen concentration. Possible explanations are high variations in natural concentrations of nitrogen between and within individual trees and seasonal fluctuations in nitrogen levels in needles.